ATM/ATR checkpoint activation downregulates CDC25C to prevent mitotic entry with uncapped telomeres - Thanasoula, M; Escandell, J; Suwaki, N; Tarsounas, M (2012)
Shelterin component TRF2 prevents ATM activation, while POT1 represses ATR signalling at telomeres. Here, we investigate the mechanism of G2/M arrest triggered by telomeres uncapped through TRF2 or POT1 inhibition in human cells. We find that telomere damage-activated ATR and ATM phosphorylate p53, as well as CHK1 and CHK2, thus activating two independent pathways to prevent progression into mitosis with uncapped telomeres. Surprisingly, telomere damage targets the CDC25C phosphatase for proteasome degradation in G2/M. CHK1/CHK2-dependent phosphorylation of CDC25C at Ser 216 is required for CDC25C nuclear export and destruction, which in turn acts to sustain the G2/M arrest elicited by TRF2- or POT1-depleted telomeres. In addition, CDC25C is transcriptionally downregulated by p53 in response to telomere damage. These mechanisms are distinct from the canonical DNA damage response to ionizing radiation, which triggers cell-cycle arrest through CDC25A destruction. Thus, dysfunctional telomeres promote ATM/ATR-dependent degradation of CDC25C phosphatase to block mitotic entry, thereby preventing telomere dysfunction-driven genomic instability. © 2012 European Molecular Biology Organization.